Analysis of Service Quality Perceptions Gap Between Students and Management of State Polytechnic of Malang - Yunia AFIATIN; Anik KUSMINTARTI; Ludfi DJAJANTO; Triesti CANDRAWATI (PT Keberlanjutan Strategis Indonesia, 2025)
Higher education institutions in Indonesia are facing increasing competition. Service quality is determined by variables such as tangiblility, reliability, responsiveness, assurance, and empathy. This research intends to investigate the gap in service quality between students’ perceptions and management at the State Polytechnic of Malang. This research uses primary data. Descriptive analysis is used to assess the level of service quality difference between the perceptions of the student and the perceptions of management. The result of this analysis is that the average value perceptions of consumers and students are smaller compared to the average value perceptions of management and service providers, which indicates that consumers remain dissatisfied with the quality of services offered by the institution. The results of this research can be used by management to identify the advantages and disadvantages of service quality and determine strategies that can meet the expectations of consumers and students.